STRATEGI DINAS PERUMAHAN, KAWASAN PERMUKIMAN DAN PERTANAHAN KABUPATEN MAMASA DALAM PENATAAN PEMUKIMAN KUMUH DI KELURAHAN MAMASA - Melkias Timbanlangi Rapa; Sjuaib Hannan; Andriani Andriani (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2020)
The purpose of this research is to find out how the strategy of the Housing, Settlement Areas And Land Services in Mamasa Regency in slum settlement arrangements in mamasa village. The research method used is a qualitative method. Data was collected using observation, interview, and documentation techniques. Meanwhile, data analysis used three components, namely data reduction, data presentation, and conclusion drawing. Analyze using three indicators of strategy implementation, namely programs, budgets and procedures. The results showed that the strategy of the Department of Housing, Settlement Areas and Land of Mamasa Regency in structuring slum settlements in Mamasa Village has been implemented properly, according to planning.